2014
DOI: 10.1016/j.foodhyd.2014.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic edible films as a new strategy for developing functional bakery products: The case of pan bread

Abstract: In the present paper, a novel approach for the development of probiotic baked cereal products is presented. Probiotic pan bread constructed by the application of film forming solutions based either on individual hydrogels e.g. 1% w/w sodium alginate (ALG) or binary blends of 0.5% w/w sodium alginate and 2% whey protein concentrate (ALG/WPC) containing Lactobacillus rhamnosus GG, followed by an air drying step at 60 °C for 10 min or 180 °C for min were produced. No visual differences between the bread crust sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(121 citation statements)
references
References 43 publications
(63 reference statements)
8
105
0
8
Order By: Relevance
“…1), which is in agreement with the findings from our previous studies (Soukoulis et al., 2014, Soukoulis et al., 2014c, Soukoulis et al., 2016). As a general trend, polysaccharide based films (PEC, LSA, HSA and κ-CAR/LBG) exerted the highest cell lethality (96.2–99.9%, please note that numbers in Fig.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…1), which is in agreement with the findings from our previous studies (Soukoulis et al., 2014, Soukoulis et al., 2014c, Soukoulis et al., 2016). As a general trend, polysaccharide based films (PEC, LSA, HSA and κ-CAR/LBG) exerted the highest cell lethality (96.2–99.9%, please note that numbers in Fig.…”
Section: Resultssupporting
confidence: 94%
“…In a previous work, we demonstrated that the inclusion of L. rhamnosus GG in edible films, comprising whey protein concentrate and sodium alginate, assisted bacterial cells to withstand heat and osmotic stress upon bread production and storage whereas it also enhanced their survival throughout ingestion and gastrointestinal passage (Soukoulis et al., 2014). In the present work, we aim to further investigate the technological feasibility of edible films comprising selected biopolymers with established good film forming properties (namely low esterified amidated pectin (PEC), low (LSA) and high (HSA) viscosity sodium alginate, porcine skin gelatine (GEL) and kappa-carrageenan/locust bean gum (κ-CAR/LBG)), in the presence or absence of whey protein concentrate (WPC) as potential vehicles for L. rhamnosus GG.…”
Section: Introductionmentioning
confidence: 99%
“…Bread Soukoulis et al (2014) formulated a probiotic bread by applying a film-forming solution (edible film) based on a binary blend containing 0.5 % (w/v) sodium alginate and 2 % (w/v) WPC inoculated with the probiotic strain Lactobacillus rhamnosus GG. Edible films are thin layers of biopolymers that can be consumed and are usually applied on the food surface by spraying or brushing.…”
Section: Whey-fermented Foods and Beveragesmentioning
confidence: 99%
“…rhamnosus GG and the viability was found to be 6.55-6.91 log cfu/30-40 g portion of bread after in vitro digestion under simulated gastro-intestinal conditions and no impact of the bread crust matrix on cell inactivation was noticed (Soukoulis et al 2014). Meat mainly in the form of sausages is also being used as an alternate to dairy based probiotic foods.…”
Section: Other Non-dairy Based Productsmentioning
confidence: 96%